2017
DOI: 10.1186/s12875-016-0578-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of a self-rating scale to monitor depression severity in recurrent GP consultations in primary care – does it really make a difference? A randomised controlled study

Abstract: BackgroundLittle information is available about whether the use of self-assessment instruments in primary care affects depression course and outcome. The purpose was to evaluate whether using a depression self-rating scale in recurrent person-centred GP consultations affected depression severity, quality of life, medication use, and sick leave frequency.MethodsPatients in the intervention group met their GP regularly at least 4 times during the 3 months intervention. In addition to treatment as usual (TAU), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Two recent trials in primary care have reported conflicting findings on the value of PROMS in improving depression symptoms 910. These studies were both small and probably underpowered to detect clinically meaningful changes in outcomes.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…Two recent trials in primary care have reported conflicting findings on the value of PROMS in improving depression symptoms 910. These studies were both small and probably underpowered to detect clinically meaningful changes in outcomes.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…In paper 1, the participants were recruited from two areas: the city of Gothenburg and its suburbs, and the middle-sized town of Skövde with rural surroundings. In Gothenburg, the FPs were recruited from an on-going RCT that evaluated whether the use of a self-rating questionnaire for severity of depression had any impact on patient outcomes [147]. All FPs had undergone a ½ day training with an experienced colleague, but not all had been in the intervention group and used the questionnaire.…”
Section: Settings For the Studiesmentioning
confidence: 99%
“…Patients can feel more involved in their care and more motivated to adhere to treatment and followup [23,24]. Primary care patients in Sweden monitored with the Montgomery-Asberg rating scale were more likely to adhere to antidepressants, but no improvements in outcome were observed in that study [25], so findings are variable and more research needed.…”
Section: Background and Rationale {6a}mentioning
confidence: 95%